Educating Resistance Civic Education and the Rise of Defensive Nationalism in Iran against the United States - Mohammad Hossein Mousavi; Amir Abbas Rahimi; Fatemeh Zahra Hosseini; Leila Ahmadi; Maryam Sharifi; Ali Reza Karimi (JOCER: Journal of Civic Education Research, 2026)
This study examines how civic education in Iran contributes to the construction of defensive nationalism amid prolonged geopolitical tensions with the United States.  While previous studies have separately explored Iranian nationalism, anti-Americanism, and civic education, limited scholarship has systematically analyzed how educational discourse mediates geopolitical conflict and transforms it into everyday understandings of citizenship and national identity in non-Western contexts. To address this gap, the study employs a qualitative research design using Critical Discourse Analysis (CDA) to analyze 12 official civic education textbooks for grades 10–12, national curriculum policy documents, and state-sanctioned instructional materials issued by the Iranian Ministry of Education between 2020 and 2025. while simultaneously promoting narratives of resistance, sovereignty, and moral obligation as core elements of citizenship. Defensive nationalism, understood as a form of nationalism oriented toward protecting sovereignty against perceived external threats, characterized by a protective orientation toward perceived external threats rather than expansionist ambitions. However, the study also finds that such narratives are not passively internalized; instead, students actively negotiate and reinterpret national identity within broader socio-cultural and global contexts. Addressing the limited scholarship on how civic education mediates geopolitical tensions through nationalist discourse in non-Western contextsanalytical and by demonstrating how education functions as a key site for the production of geopolitical consciousness and political subjectivity in contemporary Iran.